QR code based marketing in India and Japan - Bamoriya, Hemant (The European Journal of Applied Economics, 2014)
Despite the colossal growth of Quick Response Codes (QR codes) in marketing, many critics are worried about effective integration of QR code in marketing mix. The reason is the lack of knowledge about consumers’ beliefs and intentions towards QR codes. Substantial variations in exposure and adoption rate of QR code across cultures further deteriorate the application of QR code in marketing. This study intends to explore consumers’ beliefs and intentions towards QR codes in marketing across different cultures, namely India and Japan. The study also intends to analyze how the selected variables moderate the relationship between beliefs and intentions. A scenario-based experimental design was used and data was analyzed using Structural Equation Modeling and General Linear Modeling. The findings suggest a positive relationship between culture and beliefs as well as between beliefs and intentions. Further on, media and on-campaign instructions are found to be significantly moderating the relationship between beliefs and intentions. Finally, based on the key findings, the study offers some valuable perspectives on the evolving nature of QR codes in marketing and provides implications for marketers.
Keywords: QR codes; mobile marketing; marketing; Japan; India; culture